Effects of intra-operative fluoroscopic 3D-imaging on peri-operative imaging strategy in calcaneal fracture surgery - Beerekamp, M. S. H. (Arch Orthop Trauma Surg, 2017)
INTRODUCTION: Previous studies demonstrated that intra-operative fluoroscopic 3D-imaging (3D-imaging) in calcaneal fracture surgery is promising to prevent revision surgery and save costs. However, these studies limited their focus to corrections performed after 3D-imaging, thereby neglecting corrections after intra-operative fluoroscopic 2D-imaging (2D-imaging). The aim of this study was to assess the effects of additional 3D-imaging on intra-operative corrections, peri-operative imaging used, and patient-relevant outcomes compared to 2D-imaging alone. PATIENTS AND METHODS: In this before–after study, data of adult patients who underwent open reduction and internal fixation (ORIF) of a calcaneal fracture between 2000 and 2014 in our level-I Trauma center were collected. 3D-imaging (BV Pulsera with 3D-RX, Philips Healthcare, Best, The Netherlands) was available as of 2007 at the surgeons’ discretion. Patient and fracture characteristics, peri-operative imaging, intra-operative corrections and patient-relevant outcomes were collected from the hospital databases. Patients in whom additional 3D-imaging was applied were compared to those undergoing 2D-imaging alone. RESULTS: A total of 231 patients were included of whom 107 (46%) were operated with the use of 3D-imaging. No significant differences were found in baseline characteristics. The median duration of surgery was significantly longer when using 3D-imaging (2:08 vs. 1:54 h; p = 0.002). Corrections after additional 3D-imaging were performed in 53% of the patients. However, significantly fewer corrections were made after 2D-imaging when 3D-imaging was available (Risk difference (RD) −15%; 95% Confidence interval (CI) −29 to −2). Peri-operative imaging, besides intra-operative 3D-imaging, and patient-relevant outcomes were similar between groups. CONCLUSION: Intra-operative 3D-imaging provides additional information resulting in additional corrections. Moreover, 3D-imaging probably changed the surgeons’ attitude to rely more on 3D-imaging, hence a 15%-decrease of corrections performed after 2D-imaging when 3D imaging was available. No substantiation for cost reduction was found through reduction in peri-operative imaging or in terms of improved patient-relevant outcomes.